(untitled) (Bangladesh Medical Journal, 2016)
Thyroid diseases have different treatment modalities. They can be treated with various surgical procedures. The aim of the study is to find out the outcome of various thyroid surgeries. A total of 161 patients of thyroid diseases were treated by surgery in the department of ENT at Dhaka Medical College Hospital in the period of January 2014 to December 2015. Out of 161 cases, 126 (78.3%) were female and 35 (21.7%) were male having a female to male ratio of 3.6: 1. Most of the patients (28.0%) were between the age group of 31 to 40 years (mean age 35 ± 6). Most of the patients presented with multinodular goiter (59, 36.6%) & nodular goiter (54,33.5%). The patients underwent total thyroidectomy (77,47.8%), hemithyroidectomy (53, 32.9%) and subtotal thyroidectomy (22,13.7%). During the post operative period, transient recurrent laryngeal nerve palsy was found in 3 (1.9%) cases. We found in this study that, thyroid diseases are female predominant; mainly in the form of multinodular goitre which can be effectively treated by total thyroidectomy. Bangladesh Med J. 2015 Sep; 44 (3): 157-159